Zinc supplementation improves antioxidant status, and organic zinc is more efficient than inorganic zinc in improving the bone strength of aged laying hens. Issue 5 (4th August 2022) - Niknia, Aidin Dokht; Vakili, Reza; Tahmasbi, Abdol‐Mansour
Abstract: Background: There have been some reports indicating that supplementation of zinc could alleviate the negative effects of age on egg quality in laying hens. However, information regarding these positive effects on health and zinc deposition in the body is limited. Objectives: The aim of the present study was to investigate the effect of organic and inorganic sources of zinc on the antioxidant activity, bone strength, and zinc deposition in the tissues of older laying hens. Methods: In a completely randomized design, 175 Leghorn laying hens (w36) aged 80 weeks were allocated into seven treatment groups and five replications: control (without zinc supplementation), zinc sulphate treatments (15, 30, and 45 mg/kg), and organic zinc treatments (15, 30, and 45 mg/kg). Results: There was a significant increase in feed intake in the zinc sulphate and organic zinc treatments compared to the control treatment ( p  < 0.05). The egg mass in organic and sulphate zinc showed a significant increase. The feed conversion ratio was decreased significantly in the organic zinc treatments ( p  < 0.05). Both organic and sulphate zinc supplements enhanced serum superoxide dismutase activity as an antioxidant index ( p  < 0.05). The cortical thickness of the tibia was improved in laying hens receiving 30 mg/kg organic zinc. Supplementation of zinc could lead to an increase in zinc deposition in tissues, and organic zinc boosts bone strength. Conclusion: Zinc supplementation can improve antioxidant activity, feed intake, and feed conversion ratio and enhance egg mass and optimal absorption of zinc in tissues. The use of 30 mg/kg organic zinc is recommended for improving the cortical thickness of the tibia in aged laying hens. Abstract : Zinc supplementation can improve antioxidant status, feed intake and feed conversion ratio and enhance egg mass, optimal absorption of zinc in tissues. The use of 30 mg/kg organic zinc recommended for improve cortical thickness of tibia in aged laying hens